Prevalence and antimicrobial resistance patterns of Escherichia coli in the environment, cow dung, and milk of Selangor dairy farms - Veloo, Yuvaneswary; Rajendiran, Sakshaleni; Zakaria, Zunita; Ismail, Rohaida; Abdul Rahman, Salina; Mansor, Rozaihan; Syed Abu Thahir, Syahidiah (Multidisciplinary Digital Publishing Institute, 2025)
Background/Objectives: The increasing threat of antimicrobial resistance (AMR) to global public health urgently needs attention. Misuse of antimicrobials in sectors such as dairy farming has led to the emergence and spread of resistant bacteria and genes. This study investigated AMR patterns and profiles of Escherichia coli (E. coli) from various sources, including soil, effluent, cow dung, and milk. Methods: A total of 192 samples were collected, comprising environmental samples (soil and effluent), cow dung samples, and milk samples from eight dairy farms in Selangor, Malaysia. The spread plate method was employed to isolate E. coli, and all the isolates were subjected to Gram staining to identify Gram-negative, rod-shaped bacteria. The Vitek® 2 system was used for E. coli identification and susceptibility testing. Results: The prevalence of E. coli identified in the eight farms was 66.1%. A total of 360 E. coli isolates were successfully isolated, and 19.7% of the isolates presented AMR with ampicillin exhibiting the highest resistance (18.3%), followed by trimethoprim–sulfamethoxazole (8.9%). Additionally, 8.9% of them were multidrug resistant, which could be divided into 16 patterns. For the extended spectrum beta-lactamase screening, nine isolates were positive. Conclusions: This finding emphasizes the rise in resistant isolates in the growing dairy industry and underscores the urgency of addressing the potential reservoir of AMR. Therefore, essential measures such as continuous surveillance and effective antimicrobial stewardship programs are crucial for regulating veterinary antimicrobial use. Research on the mechanisms driving the development and dissemination of AMR is imperative for addressing One Health concerns.